Mechanism of action and potential therapeutic targets of TGF-β-related signaling pathway and its downstream miRNA expression in pulmonary arterial hypertension - Huang, Yimo; Ma, Wende; Guo, Cen; Su, Xiaoling (Frontiers in Pharmacology, 2025)
Pulmonary hypertension is a major cardiovascular disease characterized by the persistent elevation of pulmonary artery pressure, leading to vascular remodeling, fibrosis, and endothelial dysfunction. In recent years, the TGF-β signaling pathway and miRNAs have played important roles in the pathogenesis of PH. TGF-β regulates the proliferation, migration and fibrosis of vascular smooth muscle cells through the classical Smad pathway and non-classical pathways such as PI3K/Akt and MAPK. miRNAs such as miR-21, miR-145, and miR-204 play key roles. Among them, miR-21 promotes the proliferation and migration of vascular smooth muscle cells, miR-145 inhibits the overproliferation and fibrosis of vascular smooth muscle cells, and miR-204 alleviates vascular remodeling by inhibiting TGF-β signaling. The combination of CRISPR gene editing and an exosome delivery system can precisely regulate miRNA expression, thus providing new therapeutic targets for pulmonary hypertension.